Mapping the Landscape of Inclusive Education in Islamic Educational Contexts - Nuryana, Zalik; Wijayati, Rifky Dora; Sa’ari , Che Zarrina; Ead , Hamed A.; Malik , Shazia (Al-Misbah (Jurnal Islamic Studies), 2024)
In Islam, the concept of inclusive education is an important and timely topic that addresses the need for equitable and inclusive education for all individuals, regardless of ability, gender, social status, or background. This study aims to explore the research landscape on Inclusive Education in Islamic Educational Contexts with bibliometric methods. Data was collected with the Publish or Perish (PoP) application from a crossref database and then analyzed with the VosViewer application involving 200 databases. The surprising finding in this study is the absence of connection strength in this analysis may imply that the authors did not collaborate or connect in the dataset. In this study, authors have not connected, thus researchers in this field should build scientific links between authors and research issues. The study also shows that the clusters demonstrate how numerous factors, including national, religious, societal, and educational aspects, affect inclusive education in these locations. The clusters show that inclusive education in Islamic educational contexts is influenced by practical, policy, stakeholder, theoretical, and philosophical aspects, such as Islamic values, beliefs, and teachings and the requirements of learners with disabilities. The study emphasizes the need for equitable and inclusive education for all individuals, aligning with the principles and teachings of Islam that promote equality, dignity, and social justice. It sheds light on the contemporary relevance of inclusive education in Islamic educational settings and raises awareness of the significance of addressing the diverse needs of learners, including those with disabilities.